The Influence of Credit Risk, Operational Efficiency, Liquidity, and Profitability on Company Value (Empirical Study on Banking Subsector Companies on the Indonesia Stock Exchange for the 2021-2024 Period) - Agus Ari Widana; Henny Rahyuda; Sayu Ketut Sutrisna Dewi; Ida Bagus Ketut Surya (PT FORMOSA CENDEKIA GLOBAL, 2025)
The stock price, a gauge of firm value, reflects the market's assessment of the company's performance and prospects for the future. The company's high value indicates that investors have faith in management's capacity to allocate resources and promote sustained expansion. This study aims to investigate the relationship between credit risk, profitability, liquidity, and operational efficiency and corporate value. The study's population consists of the 40 banking subsector companies that were listed on the Indonesia Stock Exchange between 2021 and 2024. The sample strategy used in this study was non-probability sampling utilizing saturation sampling methodology. Data is taken from the company's financial filings for 2021–2024. The data analysis approach used in this study was multiple linear regression analysis using SPSS software. The results showed that while profitability has a positive effect on firm value, operational effectiveness and liquidity have a negative effect, and credit risk has no effect at all. The study's conclusions can lead the development of investment plans that provide the highest rate of return and provide a basis for strategic decisions relating to initiatives to increase business value.